2011
DOI: 10.1186/2191-0855-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant-mediated biodegradation of straight and methyl-branched alkanes by Pseudomonas aeruginosa ATCC 55925

Abstract: Accidental oil spills and waste disposal are important sources for environmental pollution. We investigated the biodegradation of alkanes by Pseudomonas aeruginosa ATCC 55925 in relation to a rhamnolipid surfactant produced by the same bacterial strain. Results showed that the linear C11-C21 compounds in a heating oil sample degraded from 6% to 100%, whereas the iso-alkanes tended to be recalcitrant unless they were exposed to the biosurfactant; under such condition total biodegradation was achieved. Only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The emulsifying activity of P. aeruginosa may be due to its ability to produce extracellular emulsifying agents or discharge of hydrocarbon degrading enzymes during growth of the isolates in the medium. This correlates with the work of researchers such as; Rocha et al (2011) and Parthasarathi and Anna (2014), who reported that variation in emulsification index and stability depend on the rate of production of extracellular emulsifying agents during hydrocarbon breakdown and organisms growth. Chakrabarti (2012) and Thandapani et al (2013) had also used these methods in the isolation of effective biosurfactant producing bacteria, adding that potent biosurfactant production is linked with emulsification efficiency of the organisms.…”
Section: Discussionsupporting
confidence: 60%
“…The emulsifying activity of P. aeruginosa may be due to its ability to produce extracellular emulsifying agents or discharge of hydrocarbon degrading enzymes during growth of the isolates in the medium. This correlates with the work of researchers such as; Rocha et al (2011) and Parthasarathi and Anna (2014), who reported that variation in emulsification index and stability depend on the rate of production of extracellular emulsifying agents during hydrocarbon breakdown and organisms growth. Chakrabarti (2012) and Thandapani et al (2013) had also used these methods in the isolation of effective biosurfactant producing bacteria, adding that potent biosurfactant production is linked with emulsification efficiency of the organisms.…”
Section: Discussionsupporting
confidence: 60%
“…It showed 79% crude oil degradation at 25 C in 3.0% w/v NaCl after 14 days (Bao et al, 2012). Rocha et al (2011) reported 6e100% degradation of C11eC21 hydrocarbons in heating oil at 20 days by biosurfactant (Rhamnolipid) producing P. aeruginosa ATCC 55925. However degradation of isoalkanes proved to be recalcitrant unless they were exposed to biosurfactant.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, several Pseudomonas isolates including two species closely associated with 16S rRNA gene sequences detected in this study (P. stuzeri, and P. alcaligenes) have demonstrated abilities to degrade PAHs such as naphthalene and phenanthrene, linear and branched alkanes, and diesel range compounds (Takizawa et al 1994;Ramos et al 1995;Whyte et al 1997;Beal and Betts 2000;Bosch et al 2000;Filonov et al 2000; Barathi and Vasudevan 2001;Tian et al 2003;Yeo et al 2003;Kaczorek et al 2011;Rocha et al 2011;Tang et al 2011;Gai et al 2012;Zhang et al 2012). Pseudomonas was one of the dominant genera encapsulated in gels from Bakken shale wells and reintroduced to flowback fluids in laboratory experiments, which substantially improved organic carbon degradation rates (Aukema et al 2014;Strong et al 2014).…”
Section: Implications For Surface Releasesmentioning
confidence: 94%